The mediating role of Quality Management in the relationship between human resource practices and organizational performance in the Greater Salt Municipality - Al-Hiyasat, Talal Saleh AbdulKarim (Journal of Economic, Administrative and Legal Sciences, 2021)
This research aimed to identify The Moderator Role of Quality Management on the Relationship between Human Resource Practices and Organizational Performance in the Greater Salt Municipality, and the research sample consisted of (27) respondents from administrators and workers in the following departments (Personnel Affairs Department, Public Relations Department, and General Bureau Department, And the Administrative and Legal Affairs Department) in the Greater Salt Municipality. The research found a number of results, the most important of which is that the general mean of all items to measure the degree of human resource practice in the following sections (Personnel Affairs Department, Public Relations Department, General Bureau Department, and Administrative and Legal Affairs Department) in the Greater Salt Municipality reached (4.27), which indicates The degree of strong agreement among the study sample members regarding the level of measurement of the degree of human resource practice in the Greater Salt Municipality, and that there is a strong degree on the availability of the practice of recruitment and selection, the level of performance evaluation, and the availability of elements for the practice of the reward system, and the practice of training and development in the Greater Salt Municipality, but it differs in terms of List them by the way they are set up and organized. The research also found that the general mean of all the measures of quality management in the Greater Salt Municipality reached (4.21), which indicates a strong degree of agreement between the study sample members of the role of the following sections (Personnel Affairs Department, Public Relations Department, General Bureau Department, and Affairs Department Administrative and Legal) in measuring quality management in the Greater Salt Municipality. As for discussing hypotheses, the research found that there is a statistically significant relationship between human resource practices (recruitment and selection, training and development, reward system, and performance evaluation) and the organizational performance in the Greater Salt Municipality. Finally, the researchers concluded that there is a significant difference in the role of quality management as a mediating variable on the relationship between human resources practices and organizational performance in the Greater Salt Municipality.